Component-oriented programming - Wang, Andy Ju An; Qian, Kai (Wiley, 2005)
Component Oriented Programming offers a unique programming-centered approach to component-based software development that delivers the well-developed training and practices you need to successfully apply this cost-effective method. Following an overview of basic theories and methodologies, the authors provide a unified component infrastructure for building component software using JavaBeans, EJB, OSGi, CORBA, CCM, .NET, and Web services. You'll learn how to develop reusable software components; build a software system of pre-built software components; design and implement a component-based software system using various component-based approaches. Clear organization and self-testing features make Component Oriented Programming an ideal textbook for graduate and undergraduate courses in computer science, software engineering, or information technology as well as a valuable reference for industry professionals.